1960
DOI: 10.1017/s002531540001331x
|View full text |Cite
|
Sign up to set email alerts
|

The motile (Crystallolithus hyalinus Gaarder & Markali) and non-motile phases in the life history of Coccolithus pelagicus (Wallich) Schiller

Abstract: A new coccolithophorid, Crystallolitkus hyalinus, was described with the help of electron micrographs by Gaarder & Markali in 1956 from preserved material in which the cells lacked the appendages. From temporary cultures set up from our September 1957 sea-water samples a coccolithophorid was isolated which appeared, under the light microscope, very similar to this newly described coccolithophorid but which possessed, as does the genus Chrysochromulina, a coning haptonema in addition to the two flagella. El… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(79 citation statements)
references
References 9 publications
(10 reference statements)
2
76
0
Order By: Relevance
“…the coccolithophores, which provide excellent documentation of an alternation between haploid and diploid generations manifested through very distinct heteromorphic phases (Kamptner, 1941;Parke and Adams, 1960, Billard, 1994. Ongoing efforts towards unveiling as many as possible of these heterococcolithophore (2n) -holococcolithophore (1n) life histories has an immediate, however, temporarily complicating impact on the nomenclatural framework established for these organisms.…”
Section: Discussionmentioning
confidence: 99%
“…the coccolithophores, which provide excellent documentation of an alternation between haploid and diploid generations manifested through very distinct heteromorphic phases (Kamptner, 1941;Parke and Adams, 1960, Billard, 1994. Ongoing efforts towards unveiling as many as possible of these heterococcolithophore (2n) -holococcolithophore (1n) life histories has an immediate, however, temporarily complicating impact on the nomenclatural framework established for these organisms.…”
Section: Discussionmentioning
confidence: 99%
“…4,8 respectively). Evidence here arises from both culture studies (Parke and Adams 1960;Rowson et al 1986; Probert unpubl.) and life-cycle associations from combination coccospheres (Samtleben and Bickert 1990;Samtleben and Schröder 1992;Winter and Siesser 1994;Baumann et al 1997).…”
Section: Life-cycles and Holococcolith Phase Differentiationmentioning
confidence: 96%
“…Evidence of this stems from culture observations of phase transitions (e.g. Parke and Adams 1960), observations of meiosis and syngamy (Gayral and Fresnel 1983), chromosome counts (Rayns 1962;Fresnel 1994), flow cytometry on cultured clones (Probert unpubl. ), and observations of combination coccospheres from natural populations (for a review refer to Cros et al 2000;Cros and Fortuño 2002;Geisen et al 2002).…”
Section: Life-cycles and Holococcolith Phase Differentiationmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the knowledge of coccolithophores has improved due, mainly, to an increase in detailed studies on these organisms using electron microscopy. The description of a number of holo-and heterococcolithophore combination coccospheres has suggested that the holo-and heterococcolithophore forms involved were part of the life cycle of the same species (Parke and Adams, 1960;Kleijne, 1991;Cros et al, 2000). In spite of this fact, the number of recognized species has increased.…”
Section: Introductionmentioning
confidence: 99%